2013
DOI: 10.5505/tjtes.2013.54782
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Mortality in Blunt Thoracic Trauma

Abstract: AMAÇKünt toraks travması, travma hastalarında sıklıkla toraks dışı yaralanmalarla birlikte görülmekte fakat mortaliteye etkisi tam olarak bilinmemektedir. GEREÇ VE YÖNTEMKünt toraks travmalı hastalar, klinik özellikler ve mortaliteye etki eden faktörler açısından değerlendirildi. BULGULARÇalışma grubu 76 hastadan (37,2±15 yıl) oluştu. Trafik kazası %63 oranıyla en sık görülen travma sebebiydi. Hastalarda görülen torasik yaralanmalar pnömotoraks (%54), kot kırığı (%42), hemotoraks (%22) ve akciğer kontüzyonu (%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Chrysou et al [8] reported an overall mortality rate of 5.5% (6 in 110 patients) and stated that there was a significant association between mortality rate and ISS, as all 6 deaths were in the group with an ISS >24. Liman et al [6] and Hasbahçeci et al [17] also noted that mortality increased with an increasing ISS. Segers et al [21] reported an overall mortality rate of 16.6% and an average ISS of 27.8 in their study that included 187 cases of thoracic trauma.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Chrysou et al [8] reported an overall mortality rate of 5.5% (6 in 110 patients) and stated that there was a significant association between mortality rate and ISS, as all 6 deaths were in the group with an ISS >24. Liman et al [6] and Hasbahçeci et al [17] also noted that mortality increased with an increasing ISS. Segers et al [21] reported an overall mortality rate of 16.6% and an average ISS of 27.8 in their study that included 187 cases of thoracic trauma.…”
Section: Discussionmentioning
confidence: 94%
“…Common associated injuries include spine injuries, extremity fractures, abdominal injuries, and head trauma. [17] In the study conducted by Chrysou et al, [8] the most common co-existing extra-thoracic injuries were extremity fractures, spine injuries, and head trauma, with an incidence rate of 76.4%, 53.6%, and 37.3%, respectively. Freixinet et al [12] reported a rate of 19.1% for extra-thoracic trauma, and mentioned that limb fracture was the most common pathology, with an incidence of 28.7%.…”
Section: Discussionmentioning
confidence: 98%
“…Clavicular, extremity, and abdominal injuries are other injuries that may be seen accompanying SF. Previous studies reported upper extremity fractures (17%-37%), lower extremity fractures (8%-26%), and abdominal organ injuries (3%-13%) together with SF (21)(22)(23)(24). In the current study, upper extremity fractures accompanying SF were determined at 24.7%, lower extremity fractures at 11.7%, clavicular fracture at 12.9%, and abdominal organ injuries at 9.1%.…”
Section: Discussionmentioning
confidence: 52%
“…In another study conducted in our country, low systolic blood pressure during hospitalization was found to be important for mortality and morbidity [14]. In Hasbahçeci et al's study [15], low systolic blood pressure and apneic breathing were found to be effective on mortality. In our study; the relationship between mortality, high pulse rate and low oxygen saturation is remarkable in GSW patients with high mortality rates.…”
Section: Discussionmentioning
confidence: 88%